In vitro anticancer potentiality and molecular modelling study of novel amino acid derivatives based on N1,N3-bis-(1-hydrazinyl-1-oxopropan-2-yl) isophthalamide - Asmaa F. Kassem; Gaber O. Moustafa; Eman S. Nossier; Hemat S. Khalaf; Marwa M. Mounier; Suliman A. Al-Yousef; Sabry Y. Mahmoud (Journal of Enzyme Inhibition and Medicinal Chemistry, 2019)
A series of N1,N3-bis (1-oxopropan-2-yl) isophthalamide-based derivatives 4–16 were prepared and their structures were confirmed by different spectral tools. The cytotoxic potentiality of novel compounds 4–16 was assessed by the MTT assay method on colon, lung and breast tumour cell lines. Compound 5 gave the most significant specificity anticancer activity with safety response on normal cell lines. In vitro enzyme assay and several apoptotic parameters were examined to elucidate the mode of action of compound 5. Molecular docking studies also were simulated to put insight and give better understanding to its structural features.